Determination of Variation of Strain Anisotropy of Wood due to change in Relative Humidity - Kalita, Kunjalata; Das, Nipan (International Journal of Computer Sciences and Engineering, 2025)
Wood is an anisotropic biological material with a multitude use. The paper describes variation of strain of wood samples due to the change in relative humidity (RH). The strain developed due to change in RH is measured by strain gauge method. In this paper, the strain is measured in longitudinal (L) and tangential (T) direction. For that purpose strain gauge is attached in the prescribed direction and the strain developed due to change in RH is recorded by data acquisition system. The developed data acquisition recorded ambient temperature, RH with temperature compensated and strain of the wood samples in different L and T direction. Strain anisotropies of two wood samples of different thickness are tested at different relative humidity conditions and the results are reported in the paper. Experimental results show that the strain developed in the wood sample is anisotropic.